The effect of mannequin and paired weight training on the results of abdominal reel in the lampung platprov athletes - Meysha Surya Widian; Frans Nurseto; Suwarli Suwarli (JUPE (Jurnal Penjaskesrek), 2019)
The problem in this study aims to determine the effect of mannequin training and pairing on the results of rolls on porprov athletes of male Lampung wrestling. The method used in this study is an experiment (true experiment), while the research design used was pre-post-test design. The population in this study was Lampung wrestling with a sample of a total population of 20 athletes from the total sample so that this study was called population research. The technique of retrieving data for the speed of this roll uses the time (stopwatch). The results showed that there was a significant effect of mannequin training and pairing on the results of stomach rolls of 0.04 0.05 with a significant effect. The conclusion of this study was that mannequin and paired exercises had a significant influence in increasing the yield of abdominal reels in plate pro-athletes in Lampung provincial wrestling son.Keywords : mannequin loads and pairs, stomach rolls, Wrestling,Masalah dalam penelitian ini bertujuan untuk mengetahui pengaruh latihan manekin dan berpasangan terhadap hasil gulungan pada atlet porprov putra gulat lampung. Metode yang digunakan dalam penelitian ini adalah eksperimen (true experiment), sedangkan desain penelitian yang digunakan yakni pre test-post test design. Populasi pada penelitian ini adalah gulat lampung dengan sampel yang digunakan keseluruhan jumlah populasi sebanyak 20 atlet dari total sampel sehingga penelitian ini disebut penelitian populasi. Teknik pengambilan data untuk kecepatan gulungan ini menggunakan waktu (stop watch). Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan dari latihan manekin dan berpasangan terhadap hasil gulungan perut sebesar 0.04 0.05 terdapat pengaruh yang signifikan. Kesimpulan dari penelitian ini adalah latihan manekin dan berpasangan memberikan pengaruh yang signifikan dalam meningkatkan hasil gulungan perut atlet pelatprov putra gulat provinsi lampung.Kata kunci : Beban manekin dan berpasangan, Gulungan Perut, Gulat.